Moving in the Mediterranean: Public Women and Their Routes - McDonough, Susan (Delaware Valley Medieval Association, 2025)
Susan McDonough, this year the George William Cotrell Jr member of the School of Historical Studies at the Institute for Advanced Studies in Princeton, is an Associate Professor of history at UMBC. A scholar of women, gender and sexuality in the medieval Mediterranean, Susan is currently at work on two projects: one is solo-authored monograph on sex workers, the other, a collaboration with Michelle Armstrong-Partida of Emory University, began with Mediterranean singlewomen and has grown to include single men, migration, shared cultures of sexuality, and gender identity. Her work has been supported by fellowships with the NEH and the Newberry Library.
Keywords: Public Women; women, gender and sexuality; Mediterranean